2016
DOI: 10.1111/medu.12896
|View full text |Cite
|
Sign up to set email alerts
|

What do UK doctors in training value in a post? A discrete choice experiment

Abstract: Trainees place most value on good working conditions, good opportunities for their partners and desirable geographical location when making career-related decisions. This intelligence can be used to develop alternative models of workforce planning or to develop information about job opportunities that address trainees' values.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 49 publications
(59 citation statements)
references
References 42 publications
2
57
0
Order By: Relevance
“…The same DCE carried out amongst final‐year medical students revealed that the relative values of the attributes were similar to those observed among trainee doctors; the most highly valued for both groups was ‘working conditions’ . The authors propose that the findings from these studies will be useful to health care organisations because the job attributes considered are those they are likely to have some control over . Hence, training positions in less popular specialties or geographic areas could be made more attractive by manipulating the attributes under scrutiny.…”
Section: Examples Of Dces From the Literaturementioning
confidence: 65%
See 2 more Smart Citations
“…The same DCE carried out amongst final‐year medical students revealed that the relative values of the attributes were similar to those observed among trainee doctors; the most highly valued for both groups was ‘working conditions’ . The authors propose that the findings from these studies will be useful to health care organisations because the job attributes considered are those they are likely to have some control over . Hence, training positions in less popular specialties or geographic areas could be made more attractive by manipulating the attributes under scrutiny.…”
Section: Examples Of Dces From the Literaturementioning
confidence: 65%
“…concerned medical trainees’ preferences for characteristics of a training post. Respondents were asked to choose between two hypothetical posts in which levels of the ‘Potential earnings’ attribute were set at 5%, 10% or 20% above average earnings . Findings from this study revealed that trainees would accept a move from a position with ‘good’ working conditions (defined by ‘rotas, amount of on‐call time, time off, staffing levels, etc.’) to one with ‘poor’ conditions if they were compensated with potential earnings of 49.8% above average earning potential (all other attributes being equal).…”
Section: Why Use a Dce?mentioning
confidence: 98%
See 1 more Smart Citation
“…In our earlier study using the DCE methodology, we examined what is important in medical careers decision making to FP and trainee (resident) doctors . That sample encompassed both newly qualified doctors and those nearing the end of training.…”
Section: Introductionmentioning
confidence: 99%
“…Different trainees will value different locations based on personal and professional circumstances but a location they consider desirable is valued highly by trainees when considering a training post. Being notified well in advance also allows trainees to plan accommodation, employment for a partner and childcare 11. Knowledge of their work schedule more than 1 month in advance was found to be associated with increased satisfaction with life overall in one cohort study of early career paediatricians 12.…”
Section: Configuration Of Specialty Training Programmesmentioning
confidence: 99%